Structures and Properties of Chitosan Based Porous Membranes (Journal of Fiber Bioengineering and Informatics, 2016)
In order to improve some defects of pure chitosan membrane, such as the high brittleness and poorflexibility etc.. This paper adopted a simple and effective method to realize the performance optimizationby blending with Poly Lactic Acid (PLA) and Poly (Vinyl Alcohol) (PVA). The result indicated thatcompared with pure CS membrane, moisture absorption rate and Water Vapor Transmission Rate(WVTR) of CS ⁄ PLAand CS ⁄ PVAblend membranes have been greatly improved. With a certain amountof the PLA or PVA, the breaking elongation of the blend membrane rise steadily. The physical propertiesof CS ⁄ PLA blend membrane are better than the CS ⁄ PVA's, so the research for CS ⁄ PLA blend membraneis expanded. With the Scanning Electron Microscopy (SEM) images, it observed that the CS ⁄ PLA blendmembrane's porosity is improved after freeze-drying, and have better porous structure, the pore size andmorphology with different blending ratios changed significantly. Besidethe SEM images, CS ⁄ PLA blendmembranes' Fourier transform infrared spectroscopy (FTIR) reveal that the strong hydrogen bondsformed between CS and PLA, which is consistent with the conclusions of the Differential ScanningCalorimetry (DSC). The DSC curve analysis shows that the decomposition temperatures of the blendmembrane decrease firstly and then increase with the decrease of CS content. The comprehensiveproperty of the porous membranes is optimal point where the CS content is 60%. The good properties,such as moisture regain, porosity, and water vapor transmission rate, of the kind of CS ⁄ PLA or CS ⁄ PVAblend membranes suggested a potential application in wound dressing.
Keywords: Chitosan (CS); Poly Lactic Acid (PLA); Poly (Vinyl Alcohol) (PVA); Lyophilization; PorousMembrane; Biodegradation